(untitled) (Journal of actual problems of jurisprudence, 2018)
This article examines the role of the prosecutor in the pre-trial stage as the beginning and during the preliminary investigation. Function Procedure manual investigation into the activities of the prosecutor in the law is not mentioned, but its presence is evident from the analysis of the actual content of the activities of the prosecutor in the pre-trial stages of the criminal process and the Republic of Kazakhstan regulatory legal acts. Opinions of various legal scholars about the role of the prosecutor in the pre-trial stage. The relations and contradictions of the issues that relate to the functions of the prosecutor. They are not Untried role in maintaining law and order in the country. Key words: criminal prosecution, obschenadzornost, public prosecutor’s supervision, procedural autonomy, management, pre-trial stage.